Effects of chronic stress and intestinal inflammation on commercial poultry health and performance: A review - Guillermo Tellez-Isaias; Wolfgang Eisenreich; Victor M. Petrone-Garcia; Inkar Castellanos-Huerta; Xochitl Hernandez-Velasco; Guillermo Tellez Jr; Walter G. Bottje; Juan D. Latorre; Roberto Senas-Cuesta; Billy M. Hargis; Makenly E. Coles; Saeed El-Ashram; et al. (German Journal of Veterinary Research)
The gastrointestinal tract provides the biological environment for nutrient digestion and absorption. Its physical and chemical barriers are crucial to protect from invading pathogens and toxic substances. On this basis, the intactness of the gastrointestinal tract, with its multiple functions and impacts, is one of the key prerequisites for human and animal health. Undoubtedly, the functions of a healthy gut system also largely benefit the welfare and performance of animals in farming systems such as poultry industries. Broiler chickens grow rapidly, as a result of rigorous genetic programs, due to the high absorption capacity of intestinal epithelia for nutrients, the quick transport of nutrients to the muscle, and their efficient conversion into energy and biomass. Due to oxygen metabolism or enteric commensal bacteria, intestinal epithelial cells create reactive oxygen and nitrogen species physiologically. However, increased generation of these oxidants goes along with the formation of free radicals resulting in oxidative stress causing lipid peroxidation and dramatic molecular changes in the structure and function of the cell and mitochondrial membranes. These effects contribute to chronic oxidative stress and inflammation of the gastrointestinal tract and generally affect all chicken organs, tissues, and cells. Hence, all forms of chronic stress, regardless of the origin, negatively impact the chicken's overall performance, health, and welfare. This review article highlights some enteric inflammation models and biomarkers to evaluate gut integrity in chickens and discusses the repercussions that chronic stress and intestinal inflammation have on the health and performance of commercial poultry.